Origin of Positive Aging in Quantum‐Dot Light‐Emitting Diodes. Issue 10 (3rd July 2018) - Su, Qiang; Sun, Yizhe; Zhang, Heng; Chen, Shuming
Abstract: The phenomenon of positive aging, i.e., efficiency increased with time, is observed in quantum‐dot light‐emitting diodes (QLEDs). For example, the external quantum efficiency (EQE) of blue QLEDs is significantly improved from 4.93% to 12.97% after storage for 8 d. The origin of such positive aging is thoroughly investigated. The finding indicates that the interfacial reaction between Al cathode and ZnMgO electron transport layer accounts for such improvement. During shelf‐aging, the Al slowly reacts with the oxygen from ZnMgO, and consequently, leads to the formation of AlO x and the production of oxygen vacancies in ZnMgO. The AlO x interlayer reduces the electron injection barrier while the oxygen vacancies increase the conductivity of ZnMgO and, as a result, the electron injection is effectively enhanced. Moreover, the AlO x can effectively suppress the quenching of excitons by metal electrode. Due to the enhancement of electron injection and suppression of exciton quenching, the aged blue, green, and red QLEDs exhibit a 2.6‐, 1.3‐, and 1.25‐fold efficiency improvement, respectively. The studies disclose the origin of positive aging and provide a new insight into the exciton quenching mechanisms, which would be useful for further constructing efficient QLED devices. Abstract : Due to enhancement of electron injection and suppression of exciton quenching, the 8 d shelf‐aged blue, green, and red quantum‐dot light‐emitting diodes (QLEDs) exhibit a 2.6‐, 1.3‐, and 1.25‐fold efficiency improvement, respectively. The origin of positive aging is investigated and insight into exciton quenching mechanisms is provided.